Muscle fibro-adipogenic progenitors from a single-cell perspective: Focus on their “virtual” secretome - Negroni, Elisa; Kondili, Maria; Muraine, Laura; Bensalah, Mona; Butler-Browne, Gillian Sandra; Mouly, Vincent; Bigot, Anne; Trollet, Capucine (Frontiers in Cell and Developmental Biology, 2022)
Skeletal muscle is a highly plastic tissue composed of a number of heterogeneous cell populations that, by interacting and communicating with each other, participate to the muscle homeostasis, and orchestrate regeneration and repair in healthy and diseased conditions. Although muscle regeneration relies on the activity of muscle stem cells (MuSCs), many other cellular players such as inflammatory, vascular and tissue-resident mesenchymal cells participate and communicate with MuSCs to sustain the regenerative process. Among them, Fibro-Adipogenic Progenitors (FAPs), a muscle interstitial stromal population, are crucial actors during muscle homeostasis and regeneration, interacting with MuSCs and other cellular players and dynamically producing and remodelling the extra-cellular matrix. Recent emerging single-cell omics technologies have enabled to dissect the heterogeneity of each cell populations within skeletal muscle. In this perspective we review here the recent single-cell omics studies with a specific focus on FAPs in mouse and human muscle. More precisely, using OutCyte prediction tool, we analysed the “virtual” secretome of FAPs, in resting and regenerating conditions, to highlight the potential of RNAseq data for the study of cellular communication.